Use of Brasil nut residues for globular cacti cultivation in the Amazon region - Gomes, Iane Barroncas; Ferreira, Milena da Silva; Queiroz, Geovana Meireles; Santos, Luís Antônio Coutrim dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
This research aimed to evaluate growth responses of three globular cacti species: Astrophytum asterias (Zucc.) Lem., Gymnocalycium anisitsii subsp. multiproliferum (P.J. Braun) P.J. Braun & Esteves e Frailea grahliana (F. Haage) Britton & Rosee cultivated in four organic substrates. The species were chosen based in their comercial value and availability of acquisition. The experimental design used was completely randomized, with 15 individuals of each species per treatment, as follows: SUB 1 (brazilian nut crushed seed coat), SUB 2 (cupuaçu fruit chushed bark), SUB 3 (brazilian nut crushed fruit bark) and SUB 4 (mixed tree barks chushed). Chemical anlysis of each material revealed importante diferences in pH values. The brazilian nut crushed seed coat provided the best results in height and diameter incremente for all species tested, being the most suitable material for use, both pure or added to Other materials in media composition recipes. Considering the physical properties and nutritional contentes, all materials have potential to be used as media to the tested species, however, it is recommended to use the cupuaçu bark and the mixed tree barks with Other componentes so that the pH can be balanced.